Analisis Perilaku Produsen Dalam UMKM Menurut Perspektif Islam - Lubis, Muhammad Rum; Iqbal, M.; Salam, Rangga (Yayasan Rahmat Islamiyah, 2024)
The aim of this research is to analyze how producers behave in facing a strategy so that the development of MSMEs runs quickly and stably, in the face of business competition. The results of this research show that the behavior of Muslim producers must be based on Islamic teachings, namely Amanah, Siddiq, Fathonah, and Tabligh. This aims to bring benefits and benefit to society and achieve blessings from Allah SWT. As Muslims we should apply consumer, producer and market behavior. In accordance with Islamic law, the activities we carry out are not only for the benefit of this world but for the benefit of the afterlife as well. This can be in line with Muslim MSMEs which transact halally and according to Islamic law.